Рівневі вимірювальні перетворювачі густини водяних суспензій - Пістун, Є.; Николин, Г. (Видавництво Національного університету «Львівська політехніка», 2000)
Considered principle of construction level measuring sensor of suspension water density invariable to level change in measuring object. Imposed possibility of apply such measuring sensor for dimension of suspension water density of grind copper ore.